PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN YOUTUBE TERHADAP PEMAHAMAN LINGKUNGAN SISWA KELAS V SDN 232 PALEMBANG - Fantri Dwi Ananta; Magdad Hatim; Ida Suryani (STKIP Singkawang, 2026)
Elementary school education plays an important role in shaping students' character and basic knowledge, including in terms of understanding the environment. However, conventional learning approaches that are textual and less interactive are still obstacles in improving students' understanding of environmental issues. This study examines if using YouTube for problem-based learning affects fifth graders' environmental comprehension at SDN 232 Palembang. The method used is the True Experimental plan approach with a Posttest-Only Control Design research plan, and tests are used to gather information. When we look at statistics, we use t-tests, homogeneity tests, homology tests, and normality tests. The study found that the experimental class scored 81.35 and the control class 72.40 on the posttest. This shows that problem-based learning with YouTube support outperforms traditional education. “The significance level of 0.05 in the t-test revealed a significant degree of 0.004 less than the 0.05 sig value, or 0.004 <0.05. Based on the t-test ttable 2.00958, which had a tcount of 3.047, Ho is not accepted and Ha is accepted. This shows that the problem-based learning model, which is helped by YouTube, has a big effect on how aware class V students at SDN 232 Palembang are of the surroundings.”